Applying Contemporary Management Principles to Implementing and Evaluating Value-Added Pharmacist Services - Shane P. Desselle; Leticia R. Moczygemba; Antoinette B. Coe; Karl Hess; David P. Zgarrick (MDPI AG, 2019)
Value-added pharmacy services encompass traditional and emerging services provided by pharmacists to individual and entire populations of persons increasingly under the auspices of a public health mandate. The success of value-added pharmacy services is enhanced when they are carried out and assessed using appropriate theory-based paradigms. Many of the more important management theories for pharmacy services consider the “servicescape” of these services recognizing the uniqueness of each patient and service encounter that vary based upon health needs and myriad other factors. In addition, implementation science principles help ensure the financial viability and sustainability of these services. This commentary reviews some of the foundational management theories and provides a number of examples of these theories that have been applied successfully resulting in a greater prevalence and scope of value-added services being offered.